Território usado e fast-food no Brasil: a rede global KFC e os estabelecimentos do circuito superior marginal da economia - Marina Araújo (2024)
This research sought to distinguish the possible manifestations of the circuits of the urban economy in the national territory in the face of the hegemonic territorial division of labor through the study of fast-food chains. We seek to analyze the performance, in Brazil, of the American chain Kentucky Fried Chicken (KFC), the third most valuable fast-food restaurant brand in the world. Simultaneously, the emergence of Brazilian franchises that were pioneers in the sale of fried chicken by the bucket in the country (Hot n’Tender, Chicken-In and Jet Chicken) was analyzed, whose emergence preceded the installation of KFC itself, and their territorial expansion strategies. The study of these three Brazilian franchises is justified by the fact that they were created before 2003, the year of the third installation of the KFC chain in Brazil and remain in activity to this day. These franchises can be considered as belonging to the upper marginal circuit of the economy whose actors – non-hegemonic – used configurations that were already ready, developing from interstices produced by the upper circuit. By studying the territorial dynamics of these Brazilian networks, it was possible to observe how, in the face of technological modernization, different agents of the urban economy develop and persist in a market of accelerated technical and normative renewal, controlled by hegemonic actors. Fieldwork was carried out with technical visits to restaurants of the national franchises studied and the global chain KFC in Belo Horizonte/MG and its Metropolitan Region and in the cities of Rio de Janeiro/RJ, Brasília/DF, São Paulo/SP and Divinópolis/MG. As methodological resources, semi-structured and unstructured interviews and distanced observation were used. Through documentary research and fieldwork it was possible to distinguish: i) less sophisticated production based on less modern technologies from the residual upper marginal circuit – whose commercialization is a result of business opportunities and whose actors express a use of the territory as a shelter – represented here by Jet Chicken; ii) production that has a certain level of sophistication, but uses less modern technologies from the upper marginal circuit – from companies, such as Chicken-In, that use forms that were already ready, often taking advantage of the interstices produced by the superior circuit itself; iii) production based on more modern technologies from the emerging upper marginal circuit – whose commercialization is the result of strategic planning and whose agents, such as Hot n’Tender, use the territory as a resource; iv) and production destined for the global market supported by a high technological level of the superior circuit, whose performance reveals the corporate use of the national territory as is done by the KFC chain. Therefore, based on the diversity and coexistence of establishments dedicated to selling fried chicken by the bucket in Brazil, we can affirm, as proposed by the original theory, that the circuits of the urban economy are communicating vessels. Given the strengthening of the upper circuit, companies such as Chicken-In, Jet Chicken and Hot n’Tender find gaps in areas where KFC has not established itself, as well as in offering menus suited to Brazilian eating habits.